2015
DOI: 10.3109/09687637.2014.993923
|View full text |Cite
|
Sign up to set email alerts
|

What is the problem?: Evidence, politics and alcohol policy in England and Wales, 2010–2014

Abstract: This article considers alcohol policy development in England and Wales under the coalition government after 2010. With a particular focus on minimum unit pricing, it examines why policy departures based on supply-side controls drawn from public health models were abandoned in favour of a restoration of policy equilibrium. This article adopts a historically informed political science perspective, drawing upon insights from John Kingdon's policy streams approach, with a focus on how the ''alcohol problem'' is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…However, this does not reflect a brokering role in relation to the development of MUP, but highlights disagreement within the party. Mapping the development of alcohol policy in England and Wales, Nicholls & Greenaway point to both 'ideological' and 'systemic' tensions in the emergence of MUP [28]. They cite ideological tensions within the coalition government between libertarian and paternalistic perspectives throughout the MUP debate and identify that support for MUP within the coalition seemed bound by shifts in focus between departments and actors.…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not reflect a brokering role in relation to the development of MUP, but highlights disagreement within the party. Mapping the development of alcohol policy in England and Wales, Nicholls & Greenaway point to both 'ideological' and 'systemic' tensions in the emergence of MUP [28]. They cite ideological tensions within the coalition government between libertarian and paternalistic perspectives throughout the MUP debate and identify that support for MUP within the coalition seemed bound by shifts in focus between departments and actors.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by findings from Finland that showed that systematic decreases in the price of alcohol were associated with increased prevalence of alcohol-related harm, especially among people with lower socio-economic status (SES) that are at increased risk of harm (Mäkelä, Herttua, & Martikainen, 2014). Despite the evidence that suggests that MUP might be an effective strategy for reducing alcohol-related harm, the English government decided not to implement MUP (or similar price reduction strategies; Gilmore & Daube, 2014), partially due to pressures from the alcohol industry (McCambridge, Hawkins, & Holden, 2014;Nicholls & Greenaway, 2015).…”
Section: Public Support For Alcohol Policymentioning
confidence: 99%
“…Also, alcohol policy in Norway is exceptionally strict, and remains so despite shifting governments and changes in method of sale (Karlsson & Österberg, 2007). Despite explicit intentions to reform alcohol policy to reduce drinking-related problems in the UK, recent UK government policy has tended to go in a more liberal direction (Nicholls & Greenaway, 2015).…”
Section: Differences Between the Uk And Norwaymentioning
confidence: 99%